Treatment of a high-volume retroperitoneal lymphocele with obstructive hydronephrosis following lymph node dissection via combined intra-lymphocele retrograde lymphangiography with glue embolization and sclerotherapy - Jonathan Bock; Vidit Sharma; Michael Jundt; Emily Bendel; Scott Thompson (Urology Case Reports)
Management of symptomatic lymphoceles typically involves sclerotherapy and lymphangiography with embolization. When many afferent lymphatic channels are supplying a large-volume lymphocele, sclerotherapy is associated with high recurrence rate. This case presents a patient who underwent retroperitoneal lymph node dissection and developed a high-volume lymphocele that was compressing the ipsilateral ureter, causing hydronephrosis. He was treated with retrograde lymphangiography, whereby contrast dye was injected through the existing lymphocele drain and afferent lymphatics were visualized upon contrast reflux. These afferent channels were embolized and the lymphocele cavity was sclerosed, leading to reduction in lymphocele output, drain removal, and normalization of kidney function.